Pengaruh Kecerdasan Emosional dan Kecerdasan Spiritual terhadap Kinerja Guru Sekolah Minggu Buddha (SMB) Chong De Se-Sumatera Utara - Yohny Yohny; Adrian Adrian; Isomudin Isomudin (Dhammavicaya : Jurnal Pengkajian Dhamma, 2024)
The research of this study was to determine the effect of emotional intelligence and spiritual intelligence on the performance of Chong De Buddhist Sunday School (SMB) teachers in North Sumatra. The independent variables in this study are emotional intelligence (X1) and spiritual intelligence (X2), and the dependent variable is teacher performance (Y). This study uses multiple regression analysis to determine the effect of emotional intelligence (X1) and spiritual intelligence (X2) on teacher performance (Y). In this study the determination of the sample using probability sampling technique with the number of samples used in this study as many as 86 respondents. This study uses primary data, data is collected by distributing questionnaires to respondents via google forms. Testing the research hypothesis using SPSS 20.0 for Windows.The results showed that emotional intelligence (X1) had a positive effect on the performance of teachers (Y) Buddhist Sunday School (SMB) Chong De North Sumatra with a correlation coefficient ry1 = 0.645 and a coefficient of determination R2= 0.416 and the regression equation: Ŷ1 = 83.503 + 0.350X1. Spiritual intelligence (X2) has a positive effect on teacher performance (Y) Buddhist Sunday School (SMB) Chong De North Sumatra with correlation coefficient ry2=0.731 and coefficient of determination R2=0.534 and regression equation Ŷ2 = 70.516 + 0.438X2. Emotional intelligence (X1) and spiritual intelligence (X2) have a positive and significant effect together on the performance of teachers (Y) Buddhist Sunday School (SMB) Chong De North Sumatra with a correlation coefficient ry12 = 0.805 and a coefficient of determination R2 = 0.648 means emotional intelligence and emotional intelligence affect 64.8% of teacher performance while the remaining 35.2% is influenced by other independent variables that are not examined in this research. The regression equation in this study is as follows: Ŷ1,2= 58.479 + 0.209X1 + 0.329X2. Based on these results, to optimize teacher performance, policies and regulations are needed to increase emotional intelligence and spiritual intelligence.